INVESTIGATIVE DIVERSION IN THE HUNGARIAN CRIMINAL PROCEDURE SYSTEM - Čvorović, Dragana S (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Abstract: The Act XC of 2017 on Criminal Procedure, which entered into force on 01 July 2018, contains significant reforms regarding investigation in criminal proceedings in Hungary. The legislation is a bold undertaking to improve the efficiency of criminal proceedings by reinterpreting the relationship between prosecution and the investigative authority, vertically separating investigations, and integrating diversionary possibilities into analyzes. It aims to overcome the weaknesses of the current system by clearly defining the procedures of responsibility for investigations and by dealing with the more uncomplicated "trivial" cases at the discovery stage. In the paper, the author provides an overview of the provisions of the Hungarian  Criminal Procedural Act that are closely related to investigations, with a particular emphasis on the possibilities of diversion and the open questions that arise in this context and that are left to case law to elaborate.
Keywords: investigation; suspension; diversion; principle of opportunity